Study of vertical electrical resistance changes in reservoir beds of Tournaisian oil deposits - S. V. Sidorov; Z. M. Rizvanova; A. A. Leontyev; N. G. Nourgalieva; S. P. Novikova (Georesursy, 2024)
The article proposes a method for rapid assessment of the initial position of oil-water contacts, oxidized oil zones, transition zones, zones of high and decreasing resistance in the Lower Carboniferous Tournaisian oil deposits at one of the oilfields of the Republic of Tatarstan. As initial data, the values of electrical resistivity of effective interlayers from the catalog of geological and geophysical data, determined from induction logging curves, were used. Well log data for more than 200 wells drilled in elevation areas were used in analysis. The change in the electrical properties of deposits vertically is considered using the average resistivity values of effective interlayers averaged over all wells. Conclusions are based on the results of the done work: according to the resistivity values in massive carbonate deposits of the Tournaisian age, it is possible to distinguish various zones of oil saturation along the vertical; initial oil saturation does not grow exponentially, as in the Leverett function, but linearly in each zone.